Discovery Learning in an Interdisciplinary Course on Finite Fields and Applications. Issue 4 (21st April 2023) - O'Neill, Christopher; Silverstein, Lily
ABSTRACT: The authors describe their approach to teaching a course on finite fields and combinatorial applications, including block designs and error-correcting codes, using a hybrid of lectures and active learning. Under the discussed classroom model, there are two lecture days and two discovery-based discussion days each week. Discussions center around group activities that build intuition for abstract concepts while avoiding excessive technical machinery. Teaching this course presents some unique challenges, as much of the content typically appears in a second course in abstract algebra, yet the students exhibit a wide range of mathematical preparation.